Variations in horizontal velocity during three consecutive take-off phases of triple jump - Dhar, K.; Phukon, A. J.; Saha, N. G. (Scientific Journal of Sport and Performance, 2024)
It was observed that athletes gradually lose horizontal velocity during the three consecutive jump phases (hop, step and jump) in triple jump. Though loss is inevitable, this horizontal velocity needed to be carried out during the three-jump sequence(1). Maximum number of literatures has only accounted the loss while foot contact with the ground. There were few studies which has been accounted the loss in the air. Thus, this study focused on the horizontal velocity across three consecutive take-off phases including the two flight phases in between. Six national Indian male triple jumpers (age: 25-28 years) purposively selected for this study. All the movements were captured on outdoor field using three high Speed action cameras at 120 frames per seconds in linear view. The kinematic data were obtained from the recorded videos by utilizing Max track and Silicon Coach pro v0.8 software. According to the nature of the data, descriptive statistics and one way ANOVA test followed by Tukey's HSD test employed. The second take-off phase stood out with a 10.25% maximum loss among the all phases. While horizontal velocity loss is acknowledgeable in triple jump, it might be suggesting a potential area for improvement lies in refining techniques for triple jumpers.